Penerapan Metode Antrian pada Layanan Kepengurusan Paspor di Kantor Imigrasi Kelas I TPI Banda Aceh - Rusdi; Rahmanizar, Cut Sarah (Medan Resource Center, 2022)
This article describes the queuing system for passport management services at the Immigration Office Class I TPI Banda Aceh. Queue can be interpreted as a long queue of service recipients who need services from one or more service facilities. Queues occur because of an imbalance between those served and their services. Some community service users at the Immigration Office Class I TPI Banda Aceh were annoyed because of the long queues to receive immigration document services and sometimes canceled them. The purpose of this study is to optimize the queuing system in the passport management service at the Immigration Office Class I TPI Banda Aceh so that there are no long queues. The queuing system is optimized with a simulation approach using discrete event simulation. The simulation results show that the best value obtained in the proposed scenario simulation model is to add queue lines to the queuing system. The results obtained are by increasing the queue line from 1 to 2 so that the queue length is reduced from 91.2068 people per hour to 54.1520 and 50.8887 people per hour.